2016
DOI: 10.1124/mol.116.103861
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ionic Channels and Insulin Secretion by Drugs and Hormones in Pancreatic Beta Cells

Abstract: Pancreatic beta cells, unique cells that secrete insulin in response to an increase in glucose levels, play a significant role in glucose homeostasis. Glucose-stimulated insulin secretion (GSIS) in pancreatic beta cells has been extensively explored. In this mechanism, glucose enters the cells and subsequently the metabolic cycle. During this process, the ATP/ADP ratio increases, leading to ATP-sensitive potassium (K ATP ) channel closure, which initiates depolarization that is also dependent on the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 192 publications
(259 reference statements)
3
21
0
Order By: Relevance
“…Inhibition of the insulin secreting process by activation of the sympathetic nervous system has been reported [18,19]. Our findings are consistent with this notion.…”
Section: Page 5 Ofsupporting
confidence: 93%
See 1 more Smart Citation
“…Inhibition of the insulin secreting process by activation of the sympathetic nervous system has been reported [18,19]. Our findings are consistent with this notion.…”
Section: Page 5 Ofsupporting
confidence: 93%
“…This signaling pathway is voltage-dependent and requires the action of Gβγ subunits [9,10]. Similarly, α 2 -adrenergic receptor activation by NA reduces insulin release in rat pancreatic β-cells [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, TTX (0.1 µg/mL, 0.31 µM) reduced the activity of VGSC in β-cells; however, insulin secretion was impaired when the islets were applied with 6 and 20 mM glucose [27]. Velasco et al also confirmed that TTX (0.1 µg/mL, 0.31 µM) decreases the amplitude of voltage spikes in pancreatic β-cells cells and the I Na [28]. However, partial inhibition in VGSC will not suppress the action potential but will decrease its amplitude, prolong the duration, increase the excitation threshold, and delay the appearance of the next action potential [25].…”
Section: Discussionsupporting
confidence: 61%
“…32,35,63 Functional and structural defects in K ATP channels impair insulin secretion leading to the onset of diabetes. 64 Our present study demonstrated an increased KCNJ8 mRNA expression at the end of IHT in both healthy and prediabetic subjects and more pronounced effect at one month after IHT in prediabetic patients. Based on the observed similarity in KCNJ8 mRNA expression among healthy and prediabetes subjects under IHT, we postulate that KCNJ8 channels may be less vulnerable during the development of diabetes.…”
supporting
confidence: 65%